Manajemen Kinerja Guru Sekolah Dasar Pascasertifikasi di Lingkungan Dinas Pendidikan Kabupaten Minahasa - Steven Mandey (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study generally aims to describe the management performance of post-certified elementary school teachers in Minahasa District. In more detailed objectives of this study are: (1) describe the performance of post-certified elementary school teachers in Minahasa District; (2) describes the development of post-certification elementary school teachers in Minahasa District. This study uses a qualitative approach, with descriptive methods and the type of research used in this study is a case study. Research using this qualitative approach researchers act as instruments as well as data collectors. The location used is the Minahasa District Education Office. The education office in Minahasa District is the oldest education office in North Sulawesi. The type of data collected in this study is narrative, data explanation from informants both oral and data in the form of written documents. Data collection techniques used in this study were participant observation, in-depth interviews and documentation studies. The data analysis technique used in this research is descriptive data analysis using interview transcripts, field notes and other materials so that researchers present their findings. The results of this study indicate that the management of elementary school teacher performance can be carried out well under the leadership of the Head of the Department of Education so that the performance of post-certified elementary school teachers can be well maintained.